Framework Design for Modular Web-based Application Using Model-CollectionService-Controller-Presenter (MCCP) Pattern - Pinandito, Aryo; Permana, Ferdika Bagus Pristiawan; Perdana, Rizal Setya (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Information system is one of the most important business supports in organizations. Web-based applications become an appropriate solution to overcome the dynamically changing environment among different units in an organization. Model-View-Controller (MVC) is a well-known design pattern in web-based application development due to the separation of an application into several parts, hence it is easy to reuse and maintain. However, such design pattern requires improvements since the information system handles business process choreography and integration between application. Therefore, modifying the interaction of object of class in a design pattern become a challenging problem. In this paper, an application framework based on Model-CollectionService-Controller-Presenter (MCCP) design pattern, which is a modification of an MVC, was proposed. The proposed framework allows multiple different applications to run and provides inter-application data exchange mechanisms to improve the data communication process between applications. Several performance comparisons with another popular web application framework are also presented.